Pump-and-treat configurations with vertical and horizontal wells to remediate an aquifer contaminated by hexavalent chromium - Bortone, Imma; Erto, Alessandro; Nardo, Armando Di; Santonastaso, Giovanni F.; Chianese, Simeone; Musmarra, Dino (Journal of contaminant hydrology, 2020)
Pump-and-treat technology is among the most used technologies for groundwater remediation. While conventional, vertical wells (VRWs) are well-known and used from long time, horizontal wells (HRWs) have been explored for remediation technologies only in last few decades. HRWs have shown to outperform vertical wells in terms of versatility, productivity and clean-up times under certain conditions. In this paper, the efficacy of an innovative pump-and-treat (P&T) configuration for groundwater remediation obtained by adopting either VRWs or HRWs technology is comparatively tested. A 3D transient finite element model of an unconfined aquifer containing a hexavalent chromium (Cr(VI)) contamination plume is considered to compare a single horizontal well configuration vs a range of spatially-optimised arrays containing vertical wells. A sensitivity analysis aimed at finding the best configuration to minimise the remediation time and the related cost is carried out by comparing different well diameters, D, pumping rates, Q, and position of wells. A comparative cost analysis demonstrates that, for the examined case-study, a single HRW achieves the clean-up goals in the same time span as for a greater number of vertical wells, but at higher price due to the excavation costs. •Remediation of an aquifer contaminated by hexavalent chromium.•3D aquifer modelling and Pump and treat technology application.•Efficiency and cost comparison of vertical wells vs horizontal wells, from single to multiple wells application.•Best performance obtained with horizontal wells.